2013
DOI: 10.4172/2157-7110.1000226
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chitosan on Textural Properties of Common Carp Cyprinus Carpio) Surimi

Abstract: The influence of different concentrations of chitosan (0.5%, 1.0% and 1.5%) on texture, color, Water Holding Capacity (WHC), viscosity and sensory properties of common carp surimi was investigated. Chitosan was added at 0.5%, 1% and 1.5% to the common carp surimi paste, stuffed in polyamide casing and heated in a hot water bath at 90 ± 2°C for 30 min. Chitosan treatments showed significant (p<0.05) effect on functional properties of resultant surimi gels as enhanced its viscosity, WHC, color, gel strength, TPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
(24 reference statements)
3
10
0
Order By: Relevance
“…This results is in agreement with the study conducted by [15] which exhibited whiter surimi gel by addition of chitosan into common carp surimi. Their data showed that the control treatment had the lowest whiteness (56.81) whereas by addition of different levels of chitosan (0.5%, 1.0% and 1.5%), the whiteness of resultant surimi gel significantly (p<0.05) improved by 8.3%, 8.8% and 11%, respectively.…”
Section: B Tvbn Ph and Whiteness Indexsupporting
confidence: 93%
“…This results is in agreement with the study conducted by [15] which exhibited whiter surimi gel by addition of chitosan into common carp surimi. Their data showed that the control treatment had the lowest whiteness (56.81) whereas by addition of different levels of chitosan (0.5%, 1.0% and 1.5%), the whiteness of resultant surimi gel significantly (p<0.05) improved by 8.3%, 8.8% and 11%, respectively.…”
Section: B Tvbn Ph and Whiteness Indexsupporting
confidence: 93%
“…Similarly, the addition of 1.5 per cent chitosan significantly improved the viscosity, water holding capacity, gel strength, hardness and whiteness of common carp (Cyprinus Carpio) surimi gel by 35.4, 19, 50.6, 40 and 11 per cent, respectively, compared to the control sample with no added chitosan (Hajidoun and Jafarpour, 2013). Also sensory panelists allocated best scores to the surimi gel with 1.5 per cent chitosan level (Hajidoun and Jafarpour, 2013).…”
Section: Chitosan and Chitooligosaccharides In Fish Fish Products And Sea Foodsmentioning
confidence: 90%
“…The addition of chitosan at the level of 15 mg/g significantly increased the breaking force and deformation of suwari and kamaboko gels prepared from barred garfish (Hemiramphus far), and a chitosan concentration of 10 mg/g produced the highest breaking force in kamaboko gels (Benjakul et al, 2001). Similarly, the addition of 1.5 per cent chitosan significantly improved the viscosity, water holding capacity, gel strength, hardness and whiteness of common carp (Cyprinus Carpio) surimi gel by 35.4, 19, 50.6, 40 and 11 per cent, respectively, compared to the control sample with no added chitosan (Hajidoun and Jafarpour, 2013). Also sensory panelists allocated best scores to the surimi gel with 1.5 per cent chitosan level (Hajidoun and Jafarpour, 2013).…”
Section: Chitosan and Chitooligosaccharides In Fish Fish Products And Sea Foodsmentioning
confidence: 95%
“…Hajidoun & Jafarpour (2013) found 47.32, 0.80, -1.20 and 0.99 for hardness, cohesivity, adhesivity and elasticity, respectively, for the carpa surimi gel made with 1.5% chitosan. According to these authors, using chitosan for the surimi preparation decreased the content of heavy chain myosin due to polymerization and, at the same time, increased the formation of cross links among these molecules, so improving the TPA.…”
Section: Texture Profile Analysismentioning
confidence: 91%